Do Community Health Centers Have Contextual Effect on the Risk of Recurrence in Patient with Tuberculosis? A Multilevel Evidence from Surakarta, Central Java - Muvida Muvida; Vitri Widyaningsih; Bhisma Murti (Masters Program in Public Health, 2020)
Background: Community Health Centers play